Postoperatory Sepsis of Abdominal Origin - Silva, Celso; Correa, Humberto; Gómez Fossati, Carlos; González Puig, Raúl; Rubianes, Carlos; Stamboulian, Daniel; Torterolo, Edgardo (Cirugía del Uruguay, 1981)
Postoperatory sepsis of abdominal origin is the most frequent type to be found in s_rgery